Pelatihan Kesehatan Dan Keselamatan Kerja Bagi Siswa SMK Kesehatan Darul Hidayah - Rosita, Riska; Ely Nastiti, Faulinda (Duta Abdimas, 2022)
Hospital employees have a very high risk of disease. To prevent and reduce the risk of these hazards, it is necessary to implement occupational safety and health efforts in hospitals. This helps in patient safety. All prospective health workers must understand the importance of occupational safety and health, one of which is students at the Darul Hidayah Health Vocational High School (SMK) Sukoharjo. So the purpose of this community service activity is to increase students' knowledge and skills about the importance of occupational safety and health to protect themselves from injury due to work accidents, as well as to prevent the risk of injury to patients. The activity method starts from the stage of work preparation, education, training, monitoring and evaluation, and reporting. The results showed a positive response from the principal and students during service activities. Now students have to understand how to use disinfectants properly, how to wash hands properly, and how to use personal protective equipment properly to prevent work accidents. In the monitoring and evaluation process, all students were able to answer all questions correctly. So it can be concluded that the implementation team has succeeded in helping to improve the knowledge and skills of Darul Hidayah Sukoharjo Health Vocational School students about health and safety efforts for health workers.